Information technology - Davies, Paul A (Oxford University Press, 2002)
Oxford Bookworms Factfiles are non-fiction readers for all ages, featuring a wide range of topics such as famous cities, sport, science, the environment and the media. Full-colour photographs complement the text and exercises at the back of each book check students' understanding. There are also ideas for extended activities and project work. The course should prove useful for cultural and cross-curricular studies.